Prognostic value of tumor deposits and their different response to neoadjuvant therapy in locally advanced rectal cancer - Di Zhou; Junjun Zhou; Bin Hu; Yinjue Yu; Yuhai Bian; Cuiping Yang; Yongrui Bai; Haiyan Chen (PLoS ONE, 2026)
Background Tumor deposits (TDs) may have a worse prognosis in rectal cancer, but their significance in the neoadjuvant era is less certain. Post-treatment TDs might even be a sign of tumor response. The present study aimed to assess the clinical significance of TDs detected before and after neoadjuvant therapy, and to investigate the impact of neoadjuvant therapy-induced TDs changes on oncological outcomes. Methods A retrospective cohort analysis using our hospital records from 2017 to 2019 was carried out. All patients received preoperative long-course chemoradiotherapy and part of them received total neoadjuvant therapy. Results A total of 132 patients with cT 3-4 N + M 0 were included. mrTDs were observed in 40 (30.3%) patients. 40% of the patients had two or more mrTDs. 64.4% of mrTDs located in the mesorectal fat. mrTDs were associated with mrT4 stage, lymph node invasion, threatened mrMRF, and positive mrEMVI. 51.4% of mrTDs positive patients achieved complete response after neoadjuvant therapy. 3‐year disease‐free survival (DFS) and overall survival (OS) were worse in mrTD positive patients (3y-DFS: 42.5% vs 73.9%, P < 0.001; 3y-OS: 55% vs 82.9%, P < 0.001). Among the patients with mrTDs, those who became ypTDs- after neoadjuvant therapy had better outcome compared to the ypTDs+ patients (3y-DFS: 52.6% vs 22.2%, P = 0.022; 3y-DMFS: 63.2% vs 27.8%, P = 0.025). Distant metastasis occurred earlier and more frequently in ypTDs+ group, and multiple metastasis were more common. ypTDs and TDs’ different response to neoadjuvant therapy were prognostic factors of overall survival in multivariate analysis. Conclusions The presence of mrTDs and the poor regression of mrTDs in cT 3-4 N + M 0 rectal cancer after neoadjuvant treatment are associated with advanced disease and worse outcome. Patients with ypTDs+ after neoadjuvant therapy have dismal outcome, which call for more innovative treatment.